Diabetes education: a global perspective. (July 2015) - Chaney, David
Abstract Diabetes education has been acknowledged as the cornerstone of good diabetes care and management. Although evidence to support the need for diabetes education has grown in recent years, many people with diabetes remain unable to access or choose not to attend diabetes education for a variety of reasons. In order to improve the likelihood of success, diabetes education needs to be adequately resourced and tailored to meet the needs of specific populations. This paper seeks to offer a global perspective on the current status of diabetes education. Insight is provided into recent evidence suggesting poor integration of diabetes education across the globe. Finally, issues such as the need to tailor education and increase international collaboration are addressed. Copyright © 2015 John Wiley & Sons.